Evaluation of The Flipped Classroom Model on Students' Academic Achievement and Retention in MAN 1 Ambon - Rumahlewang, Emma; Lokollo, Lamberthus J.; Lasaiba, Mohammad Amin (Journal of Innovative Science Education, 2024)
This study evaluates the impact of computer simulation and animation instructional packages in natural sciences on high school student's academic achievement and retention in a flipped classroom setting. Using a quasi-experimental pre-test and post-test design, 30 students used the computer simulation package, and 29 students used the computer animation package. Data were collected via academic achievement and retention tests and analyzed using descriptive statistics and independent sample t-tests. The results showed significant improvements in academic achievement for both groups. The average post-test score increased from 28.52 to 70.35 in the computer simulation group and from 25.74 to 64.23 in the computer animation group. The t-test indicated no significant difference in academic achievement between the two groups (t = 1.98, p = 0.79). Retention scores showed a slight decrease from post-test to retention test but remained high, with average retention scores of 68.74 for the simulation group and 61.15 for the animation group. The t-test also revealed no significant difference in retention between the groups (t = 1.12, p = 0.66). The implications of this study suggest that using educational technology, such as computer simulations and animations, in a flipped classroom setting can significantly enhance students' academic achievement and knowledge retention. It underscores the importance of integrating technology into the educational curriculum to create a more inclusive, interactive, and effective learning environment. Additionally, these findings allow educators to choose the teaching methods that best suit their instructional needs and contexts, whether in resource-limited situations or when teaching complex concepts.